What is the role of innovation in productivity growth in Central and Eastern European countries? - Tevdovski, Dragan; Toshevska trpchevska, Katerina; Makrevska disoska, Elena (Wiley-Blackwell on behalf of the European Bank for Reconstruction and Development, 2017)
The paper uses company level data from the Eurostat’s Community Innovation Survey 2008 and applies CDM model in order to estimate the links between R&D engagement, R&D intensity, innovation output and productivity in selected Central and Eastern European Countries – Bulgaria and Romania, and compares their performance with Germany. The results showed that different processes drive company's decision to engage in R&D in Bulgaria and Romania in comparison to Germany; R&D intensity is an important factor of product innovation in the observed CEE countries and product innovation leads to higher productivity in Bulgaria and Romania, while process innovation leads to higher productivity in Bulgaria, but not in Romania.
Economics of Transition recently changed its name into Economics of Transition and Institutional Change
Keywords: innovation; productivity; Community Innovation Survey 2008; Central and Eastern European countries; CDM model